DNA adducts as a dosimeter for risk estimation. - Belinsky, S A (1987)
The dose response for O6-methylguanine (O6MG) formation and cytotoxicity was determined in lung and nasal mucosa from Fischer 344 rats during multiple dose administration of the tobacco-specific nitrosamine-4-(N-methyl-N-nitrosamino)-1-(3-pyridyl)-1-butanone (NNK). O6MG accumulated in the lung following treatment for 12 days with doses of NNK from 0.3 to 100 mg/kg/day. The dose response for NNK was nonlinear; the O6MG-to-dose ratio, an index of alkylation efficiency, increased dramatically as the dose of carcinogen decreased. These data suggest that low- and high-Km pathways may exist for activation of NNK to a methylating agent. Marked differences in O6MG concentration were observed in specific lung cell populations. The Clara cell, one of the suggested progenitor cells for nitrosamine-induced neoplasia, was found to possess the greatest concentration of O6MG. Moreover, as the dose of NNK was decreased from 100 to 0.3 mg/kg, the alkylation efficiency in this cell population increased 38-fold. The presence of a high-affinity pathway in the Clara cell for activation of NNK may contribute to the potent carcinogenicity observed following low-dose exposure to this tobacco-specific carcinogen. The dose response for O6MG formation differed considerably between the respiratory and olfactory mucosa from the nasal passages of the rat. The dose response was nonlinear in respiratory mucosa but linear in olfactory mucosa. The alkylation efficiency increased dramatically only in the respiratory mucosa as the dose of NNK was decreased. These studies suggest that a low Km pathway for NNK activation is also present in the nose and that this pathway is localized predominantly in the respiratory region.(ABSTRACT TRUNCATED AT 250 WORDS)